Text Comprehension and Learning Interest on Online News as Teaching Material During Covid-19 (A Critical Discourse Analysis on Articles at Jakarta Post Online News) - Prayogo, Lego; Pipit, Mayang (Universitas Indraprasta PGRI, 2023)
The purpose of this study is to analyze and describe critical discourse on text elements and social cognition on learning interest in online news texts during the COVID-19 pandemic in Indonesia on The Jakarta Post website. The research method used is descriptive qualitative. This study uses Teun Van Dijk's Critical Discourse Analysis theory, namely text analysis and social cognition. The results show that the three analyzed texts show that the macrostructure of The Jakarta Post uses appropriate and representative themes, as well as the superstructure uses neutral headlines. Microstructure analyzes the semantic, syntactic, stylistic, and rhetorical elements that present their meaning directly without prologue at the semantic level, and at the syntactic level, it uses an appropriate and systematic structure of subject or noun combinations, as well as the style of language used is simple. Whereas in the social cognition element, there is the ideology of The Jakarta Post journalists in producing a discourse in news texts. From the three news reports, the pro-government journalists can be seen from all the decisions made by the government towards schools, parents, and students regarding interest in learning during the COVID-19 pandemic which was dominated by the government in the text. In this case, students' interest in learning was low during the pandemic. This was due to the power of government and the ideology of The Jakarta Post journalists so that the COVID-19 pandemic became a top priority, no longer a learning interest or maximizing education.